Case Control Studies in Medical Research - Sathian, Brijesh; Sreedharan, Jayadevan; Mittal, Ankush; Chandrasekharan, Nishida; Baboo, Suresh N; S, Abhilash E; E, Rajesh; Dixit, Shyam Bihari (Nepal Journal of Epidemiology, 2011)
Case-control studies can yield important scientific findings with relatively little time, money, and effort compared with other study designs. Investigators implement case-control studies more frequently than any other analytical epidemiological study. Unfortunately, case-control designs also tend to be more susceptible to biases than other comparative studies. Although easier to do, they are also easier to do wrong. A good design should aim to minimise error and bias. All remaining sources of error and bias should be recognised and decisively evaluated. Case-control studies that are well designed and carefully done can provide useful and reliable results. Investigators must, however, devote painstaking attention to the selection of control groups and to measurement of exposure information. When the number of cases is small, the ratio of controls to cases can be raised to improve the ability to find important differences. Although no ideal control group exists, readers need to think carefully about how representative the controls are. Poor choice of controls can lead to both wrong results and possible medical harm. Awareness of these key elements should help readers to identify the strengths and weaknesses of a properly reported study. Keywords: Bias; Effect size; Confounding DOI: http://dx.doi.org/10.3126/nje.v1i3.5569 Nepal Journal of Epidemiology 2011;1(3) 77-80